2020
DOI: 10.22541/au.159620968.84116387
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decreased eosinophil counts and elevated lactate dehydrogenase predict severe COVID-19 patients with underlying chronic airway diseases

Abstract: Background: Several predictors for the severity of coronavirus disease 2019 (COVID-19) have been reported, including decreased circulating lymphocytes and eosinophil counts. However, chronic airway in ammation characterized by accumulated lymphocytes or eosinophils may affect the pathogenesis of COVID-19. We aimed to investigate the predictors for the severity of COVID-19 in patients with chronic airway diseases. Methods: In this retrospective cohort study, we reviewed medical records of all laboratory-con rme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Moreover, research has revealed that Omicron is more prevalent in Africa and Asia, and less common in Europe and North America (16). Recently, the use of cycle threshold (Ct) values of genes associated with Omicron infection has gained attention as a potential predictor of viral load (17)(18)(19). Additionally, previous reports have indicated that Ct values for COVID-19 correlate with serum biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, research has revealed that Omicron is more prevalent in Africa and Asia, and less common in Europe and North America (16). Recently, the use of cycle threshold (Ct) values of genes associated with Omicron infection has gained attention as a potential predictor of viral load (17)(18)(19). Additionally, previous reports have indicated that Ct values for COVID-19 correlate with serum biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of mortality in patients infected with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) increases several-fold for those with multiple comorbidities [ 1 ]. Some of these comorbidities include chronic bronchitis [ 2 ], hypertension [ 3 ], and coronary artery disease [ 4 ]. However, the risk of mortality due to SARS-CoV-2 is unclear in patients with asthma [ 5 ].…”
Section: Introductionmentioning
confidence: 99%